A method for determining the characteristics of the steady creep of a single crystal alloy - Yevhen Nemanezhyn; Gennadiy Lvov; Yuriy Torba (Авіаційно-космічна техніка та технологія, 2022)
The subject of this article is the phenomenon of material destruction during creep, as one of the most dangerous and damaging effects on turbine blades in the conditions of their operation. Considering the strength of the turbine blades of aircraft engines and power plants, note that the mechanism of cracks in the creep process is largely due to the peculiarities of the crystal structures of the blades and the properties of these structures. At this stage of development of world technologies, turbine blades are made by single crystal casting and directional solidification. These types of crystal structures are characterized by the anisotropy of their properties. The reason for the anisotropy of crystals is that the ordered arrangement of atoms, molecules, or ions in the interaction between them and the interatomic distances (as well as some unrelated direct relations, such as polarization or electrical conductivity) differ in different directions. The article pays special attention to the consideration of the creep model of an anisotropic alloy with a monocrystalline structure. The natural way to determine the material parameters of the theoretical material model is to conduct the required number of basic experiments. Numerical modeling using the known creep properties of single crystals is an alternative possibility to determine the parameters of the material. The algorithm described in this article allows us to determine all the average creep properties of a single crystal. The parameters of the described ratios can be obtained either because of direct experiments, or on the basis of micromechanical analysis, as in the case of composite materials. This article considers an example of obtaining some characteristics of the single-crystal alloy ZhS-32 because of the approximation of its creep curves, obtained experimentally. Based on Norton-Bailey's law and using the modern calculation system Maple Release 2021.0, the minimum creep deformation rate and creep constants are determined, and a graph of the creep deformation rate dependence on the material load level is plotted.